Influence of edge crack on frequencies of thin plate in bending - Luong, Nguyen Thi Hien; Giang, Vuong Quang (Vietnam Journal of Mechanics, 2005)
This paper investigates the influence of crack location and crack length on changes in natural frequencies of bending thin plate. To perform this analysis, a computing program called CRACK-PLATE, using the finite element method based on the Ressner-Mindlin' theory of plate is developed. In order to achieve a high accuracy, an isoparametric element of Barsoum is combined with an 8-node quadrilateral isoparametric element. The numerical results show that the natural frequencies are very sensitive to the crack presence in the bending thin plate. This study is a basis for crack identification based on natural frequencies of plates.